Verbs of Reporting in Academic Writing - Hladonik Gergely; Гладоник Гергель (Мукачівський державний університет, 2020)
Abstract. Reporting is an important linguistic phenomenon in academic writing. Writers introduce background of current research and review previous studies to ‘create a research space’. Making reference to claims, activities and findings of previous researchers and evaluate them appropriately is crucial in constructing a research paper. Reporting in academic writing serves a range of purposes: to present what has been done as well as what has not been done in a field; demonstrate the writer’s familiarity with the field; as tools to persuade; to locate the writer’s work in the larger context. The major source of data considered for this study is a collection of articles from the “International Journal of Language and Linguistics”, “International Journal of Literature and Arts” and “Education Journal”. These three journals were purposively selected. The journals mentioned above were chosen because they regularly publish stories and reach out to a large percentage of the reading public.

Резюме. В академічній писемності непряма мова являється важливим мовознавчим явищем. При складанні дослідження дуже критичним є відповідно посилатися на твердження, висновки та результати інших. В академічному стилі непряма мова відіграє важливі ролі - вказує на те, що досягли і те, що досліджувалося в певних сферах; показує компетентність науковця в даній сфері. Тема роботи:найбільш вживані приклади, які вказують на дієслова непрямої мови у спеціальному середовищі. Головні джерела даних зібрані зі статтей нижченаведених журналів: „International Journal of Language and Linguistics”, „International Journal of Literature and Arts”, „Education Journal”.
Keywords: reporting verbs; academic writing; prominence; information prominent; author prominent